Factor structure and psychometric properties of a Romanian translation of the Body Appreciation Scale-2. (December 2017) - Swami, Viren; Tudorel, Otilia; Goian, Cosmin; Barron, David; Vintila, Mona
Highlights: Romanian Body Appreciation Scale-2 (BAS-2) scores have adequate psychometric properties. BAS-2 scores have a one-dimensional factor structure in women and men. BAS-2 scores did not evidence sex invariance. BAS-2 scores have adequate convergent validity and test–retest reliability. Abstract: We examined the psychometric properties of a Romanian translation of the 10-item Body Appreciation Scale-2 (BAS-2). A total of 453 university students from Romania completed the BAS-2, along with measures of disordered eating, self-esteem, satisfaction with life, and subjective happiness. In addition, a separate sample of university students ( N  = 109) completed only the BAS-2 at two time-points three weeks apart. Principal-axis factor analysis indicated that BAS-2 scores had a one-dimensional factor structure in both women and men. Confirmatory factor analysis indicated that this factor structure had adequate fit, but invariance across sex was not supported. Further analyses indicated that BAS-2 scores evidenced internal consistency, convergent validity, and test–retest reliability in both women and men. These results suggest that BAS-2 scores reduce to one dimension in Romanian adults, but the lack of sex invariance may indicate that the same latent construct is not being measured in women and men.